Peningkatan Kemampuan Berhitung Permulaan Melalui Alat Permainan Edukatif Pohon Hitung Di TK Pelangi Kasih - Mutiara Magta; Shirley Shirley; Sri Wahyuni (Sentra Cendekia, 2023)
This study aims to describe the process and results of increasing initial numeracy in children aged 4-5 through an educational tree counting game at Pelangi Kasih Kindergarten, North Jakarta, in 2023 with six research subjects. This research method is classroom action research, namely the use of qualitative data analysis techniques and quantitative data analysis techniques. Using qualitative data analysis techniques, they collected data through anecdotal notes, observation sheets, and children's worksheets. Data collection and recording were conducted to determine the increase in the percentage ability to start counting in children aged 4-5 years, so quantitative data analysis techniques were used. The results of pre-research data on class A numeracy skills were 49.17%, increasing to 73.6% in cycle one activity and cycle 2 to 89.7%. The conclusion obtained from the research data results is that the counting tree educational game tool is proven to improve early numeracy skills in children aged 4-5 years at Pelangi Kasih Kindergarten, North Jakarta. The implications obtained from the results of this study are natural or concrete early childhood learning processes in learning activities in the classroom. Teachers can motivate children, provide stimulation, provide examples, and conduct question-and-answer activities so that teachers can maximize children's development.